Genome-centric metagenomics analysis revealed the metabolic function of abundant microbial communities in thermal hydrolysis-assisted thermophilic anaerobic digesters under propionate stress - Zhang, Liang (2022)
The ecological roles of microbial communities and how they interact with each other in thermal hydrolysis process (THP) assisted thermophilic anaerobic digestion (THP-AD) reactors remain largely unknown, especially under propionate stress. Two thermophilic THP-AD reactors had methane yield of 240-248 mL/g VSadded, but accumulated approximately 2000 mg/L propionate. Genome-centric metagenomics analysis showed that 68 metagenome-assembled genomes (MAGs) were recovered, 32 MAGs of which were substantially enriched. Firmicutes spp. dominated the enriched microbial community, including hydrolytic/fermentative bacteria and syntrophs. Methanogenic activities were mainly mediated by Methanosarcina sp. and Methanothermobacter spp. In addition to hydrogenotrophic methanogens, Thermodesulfovibrio sp. could also be a vital H2 scavenger, contributing to maintaining low H2 partial pressure in the bioreactors. The remarkable accumulation of propionate could be likely attributed to the weak syntrophic propionate-oxidizing activity or its absence. These findings advanced our knowledge about the mutualistic symbiosis of carbon metabolism in thermophilic THP-AD reactors.